Wastewater characterization from chemical dyeing process of silk: case study household Thai silk production, One Tumbon One Product (OTOP), Surin Province - Changsuphan, Amornpon; Thongsri, Tepwitoon; Petchkaseam, Surat; Kitchainukul, Waraporn; Lertkanavanichakul, Chanin; Tipviset, Natawan; Tirapitayanon, Wasan; Muangkaew, Kanya; Palee, Nimit; Srisaen, Jirachatr; Thonganan, Veerapat; Nartmanee, Pornvipa (Bulletin of Applied Sciences, 2015)
Household Thai silk production under One Tumbon One Product (OTOP) project can contribute the sustainable career and income to the local. However, household Thai silk production processes produce a number of wastewater. The chemical dyeing process is the process which produces wastewater. This wastewater usually discharges to the environment without any treatment. This study aims to characterize the quality of wastewater from chemical dyeing process prior to design the simply wastewater treatment system for household. Surin province which located at the northeast of Thailand was the sampling location. Totally 8 samples of wastewater from chemical dyeing process were collected from 4 different districts. The key parameters to characterize the wastewater are color, pH, chemical oxygen demand (COD), suspended solids (SS), total dissolved solids (TDS) and heavy metals. The results illustrate that wastewater from chemical dyeing process had pH 1.7-8.8, COD 1,847-3,439 mg/L, SS 271-1,200 mg/L and TDS 3,00022,739mg/L which was over Thailand national standard for wastewater except for pH. There was only 1 sample that over Thailand national standard for wastewater. The color was 196- 10,950 ADMI which over the USA guidelines (no Thailand national standard).In the case of heavy metals, there were very low concentrations were detected and they were in acceptable range when compared with Thailand national standard for wastewater.